2007
DOI: 10.1080/00365590601068983
|View full text |Cite
|
Sign up to set email alerts
|

Residual urine after intermittent catheterization in females using two different catheters

Abstract: In most females, the SpeediCath Compact catheter is at least as efficient at emptying the bladder as more conventional female catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Mean residual urine volumes reported by other authors range between 9 and 40 ml. [4][5][6] Notable is the wide variation in measured volumes, between 0 and 250 ml, in the present study. Nevertheless, relevant residual urine volumes 450 and 4100 ml were only observed after 6% (n ¼ 7) and 3% (n ¼ 4), respectively, of all catheterizations (n ¼ 120).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Mean residual urine volumes reported by other authors range between 9 and 40 ml. [4][5][6] Notable is the wide variation in measured volumes, between 0 and 250 ml, in the present study. Nevertheless, relevant residual urine volumes 450 and 4100 ml were only observed after 6% (n ¼ 7) and 3% (n ¼ 4), respectively, of all catheterizations (n ¼ 120).…”
Section: Discussionmentioning
confidence: 71%
“…Wide variations in residual urine volumes after IC in some study participants were also observed by other authors. 5 Interestingly, some individuals able to apply correct IC techniques do not always succeed in emptying their bladder sufficiently. However, an insufficient bladder evacuation seems to get compensated during the next catheterization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample size Assuming a non-inferiority limit of a ±20-ml difference in RU volume and an estimated corresponding standard deviation of 4.7 ml (derived from a previous study 4 ), the estimated required sample size for this crossover noninferiority trial (one-sided significance level, 2.5%; power, 90%) was six subjects per sequence group. It was decided, however, to include approximately 36 subjects (to collect evaluable test results from 30 subjects) so that the study could be considered safe against inexact assumptions and provide enough power to allow for the reliable testing of secondary end points.…”
Section: Methodsmentioning
confidence: 99%
“…Shorter catheters may allow more discreet use, an attribute that has been identified as important by users of intermittent catheters. 4 The aim of this study was to evaluate the SpeediCath Compact Male catheter in terms of its performance, safety and subject acceptance when compared with a standard-length male intermittent catheter.…”
Section: Introductionmentioning
confidence: 99%